Development and optimization of an innovative raft-forming antiemetic gastro-retentive system - Mina Safa Aziz; Methaq Hamad Sabar (Pharmacia)
Gastro-retentive drug delivery systems are vital for enhancing bioavailability and prolonging gastric residence time, especially for drugs with a short half-life like Ondansetron HCl. This study developed a raft-forming gastroretentive drug delivery system using a polyelectrolyte complex (PEC) of Chitosan and anionic polymers to improve stomach retention, regulate drug release, and enhance therapeutic efficacy. Various formulations were optimized based on polymer type, ratio, cross-linking agent concentration, and hydroxypropyl methylcellulose (HPMC K100M). The best formulation (F12: Chitosan: Carbopol 934) showed high entrapment efficiency (98%), drug loading (11.5%), buoyancy (>12 hours), extended drug release (over 12 hours), and a swelling ratio of 1584% at 8 hours. FTIR and DSC confirmed PEC formation and stability, while FE-SEM demonstrated homogeneity. Drug release followed non-Fickian kinetics, indicating that both diffusion and matrix relaxation contributed to the drug release. This PEC-based system shows promise for sustained stomach delivery of Ondansetron HCl, improving therapeutic efficacy and patient adherence.